Especificidade de hospedeiros por Struthanthus aff. polyanthus (LORANTHACEAE) em uma área de cerrado, Uberlândia, Minas Gerais - Arruda, Rafael Soares de (2004)
The aim of this study was to verify if Struthcmthus aff. polyanthus presents host specificity in cerrado. Is also discussed if the abundance of the hosts and architecture of the twigs have influence in the relation of specificity. An area of 1,3 ha was sampled registering the occurrence of the mistletoe. The twigs of the hosts were classified in vertical or horizontal, and the bark in smooth or rugous. It was observed a total of 666 individuais (38 genera and 47 species), and 118 individuais (17,7%) were infested by S. aff. polyanthus, being that 91 belonged only to three species Styrax ferrugineus, Pouteria ramiflora and Kielmeyera coriacea. The abundance of S. aff. polyanthus was significantly affected by the type of bark, but not for the inclination of the twigs. In the cerrado, S. aff polyanthus seems to be generalist, but with some preference by host, mainly in function of its morphologic and ecological characteristics, as the presence of rugous bark and the host susceptibility. Moreover, the behavior of the birds seems to be important in the establishment of associations host-hemiparasitics. Being common species in the tropics and important to frugivorous birds, studies with mistletoes must be stimulated, mainly in the cerrado, one of natural ecosystems endangered.